Is policy or meritocracy? Doorway entry and stay in the system of career in Colombia (2015)
This document allow analyzing the currently situation of the Colombian career system and knowing the factors that have prohibited to perform the implementation of the administrative career like a technical system of human resource management to the service of the state. Having into consideration that developing countries have models of management of public function, it show like an organized and included structure, implement processes of selection and continue training for the exercise of the post. The administrative career is a resource that permits the state guarantee the provision of missionary services with quality and efficiency, and at the same time it defines that the political representatives exert influences as a result of client ́s relationship; that reduce the public employment to comply with soft job and particular interests. However, it is also relevant to stress the importance of professionalizing the services offered and the importance of consistency and relevance of education and training required by each of the staff members performing tasks of public administration tasks. Finally, even though in Colombia the state bodies like CNSC and DAFP are dedicated to regulate all about this topic, it is still a paper issue and continues with a limited conformism to the expedition of laws, without control nor applicability; paradigms that are broken with government programs that are focused in the objectivity and measuring of results for the term in the administrative career.